Fatty Acid Composition of Some Malaysian Seaweeds - Wan-Loy, Chu; Mohamed, Norazmi; Siew-Moi, Phang (Malaysian Journal of Science, 2003)
Lipid content and fatty acid composition of nine species of seaweeds (three Rhodophytes, two Chlorophytes and five Phaeophytes), collected from various locations along the west coast of the Peninsular Malaysia, were determined. Of the seaweeds studied, Dictyota dichotoma (Phaeophyta) contained the highest amounts of lipids (17.6% ash-free dry weight) while the Rhodophyte Gracilaria changii had the lowest lipid content (1.1% ash-free dry weight). Fatty acid composition of the seaweeds consisted of 16:0, 16:1, 18:0, 18:1, 18:2, 18:3ω3, 20:1, 20:2, 20:3, 20:4ω6 and 20:5ω3. Saturated fatty acids, particularly 16:0 were dominant, ranging from 51.2 to 84.4% total fatty acids. Except for Grocilaria changii, all the seaweeds produced eicosapentaenoic acid (EPA, 20:50ω3), which ranged from 2.4 to 10.7% total fatty acid. Gracilaria edulis from Sungai Pulai had the highest amount of 20:5ω3; however, the same species from Pulau Kukup contained only low amounts of the fatty acid (5.7% total fatty acids). Malaysian seaweeds are of good nutritional value in terms of their appreciable amounts of long chain polyunsaturated fatty acids.